Analysis of Tourist Perceptions on Service Quality and Language Proficiency at La Brisa Bali - Murtono, Putu Agus; Mahardika, I Made Ojes; Manuaba, Ida Bagus; Ardana, I Komang; Utama, I Putu Sagita Jaya (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2025)
Tourism is a strategic sector that significantly contributes to Indonesia’s economy, especially in Bali as an international destination. Service quality and staff language proficiency are important factors in shaping a satisfying tourist experience. This study aims to analyze tourists’ perceptions of service quality and staff language proficiency at La Brisa Bali, a popular beach club in Canggu, Bali. A quantitative approach with a descriptive-verificative method and purposive sampling technique was used to collect data from 80 tourist respondents. Service quality measurement refers to the five SERVQUAL dimensions (tangibles, reliability, responsiveness, assurance, empathy), while language proficiency was assessed based on fluency, clarity of communication, and the use of foreign languages, particularly English. The results show that tourists rate La Brisa Bali’s service quality as good to very good, with an average score of 4.25. The reliability dimension received the highest score, indicating consistent and dependable service that satisfies visitors. Staff language proficiency also received a good rating (average 4.10), supporting effective interaction with international tourists. However, there remains room for improvement in staff responsiveness, empathy, and communication skills. These findings provide a strategic basis for La Brisa’s management to enhance service quality and staff language proficiency, aiming to strengthen tourist loyalty and maintain its reputation as a premium tourism destination in Bali.